Compact MIMO antenna using dual-band for fifth-generation mobile communication system - Debani Prasad Mishra; Kshirod Kumar Rout; Surender Reddy Salkuti (Institute of Advanced Engineering and Science, 2021)
This paper presents the design of a multiple-input and multiple-output (MIMO) antenna for a fifth-generation (5G) smartphone that will work in dual-band. The antenna proposed in this work operates at 2 frequency ranges, i.e., (3300-3600) MHz and (4800-5000) MHz. The antenna design consists of four antennas that are placed perpendicular to the edge of the system and this makes it different from the traditional 5G antennas. The area of each antenna on the side frames is (3.9×17 mm), and hence can be used in ultra-thin smartphones for 5G applications. The reflection coefficient obtained in the simulations is less than -6 dB for the required band, which suggests that the required impedance matching is obtained. The antenna proposed is designed by using central time zone (CST) microwave studio.